THE MIDDLE EAST; DETERRENCE AND NUCLEAR DETERRENCE (Journal of the Spanish Institute for Strategic Studies, 2018)
With the signature of the controversial nuclear agreement with Iran,the Middle East could reshape once again its regional equilibrium anddeterrence logics. Nevertheless, this historical moment brings one more timean opportunity to review the deterrence theory, its weakness and strengthensbut above all, represents a chance to look into the future alternatives toweapons of mass destruction as arms controls initiatives or regionaldisarmament processes. Without being an easy process with just a singleand correct answer, this paper examines the current evolution of the theoryas well as in the Middle East case analyzing its future plausible options